Los contenidos de las web de los archivos históricos estatales. El ciudadano más cerca de la información - García González, María; Chain Navarro, Celia (Cuadernos de Documentación Multimedia, 2009)
We show the current state of web pages of the three Spanish national historic archives (Archivo Historico Nacional, Archivo General de Indias y Archivo General de Simancas) the information about the quality of information that they offer. Thus we defined a group of parameters and indicators that show us additional information about these pages, to frid out if they haven a high or low level. We concluded that there are no substantial differences between the three archives. The navigation of their web pages is easy and pleasant since the structure, design and colours of the pages are suitable. However, it would be helpful to increase the size of the text. The structure of theinformation should be improved as well as the incorporation and updating of some content, and also define planning and present their services.